Clinical outcomes following PD-1 inhibitor elective discontinuation in cutaneous squamous cell carcinoma: exploring treatment de-escalation - Itamar Averbuch; Nofar Edri; Nethanel Asher; Gal Markel; Daniel Hendler; Hadas Ditzian Kugler; Eyal Yosefof; Noga Kurman (Cancer Immunology, Immunotherapy)
Abstract Background Non-melanoma skin cancers (NMSC) are the most common malignancies worldwide. While early-stage lesions can be definitively treated with local therapies, advanced stage cutaneous squamous cell carcinoma (cSCC) often requires systemic treatments such as PD-1 inhibitors. These treatments may be administered for prolonged durations; this practice may lead to an unnecessary physical and financial toxicity. The purpose of this study was to evaluate the patterns of disease progression after anti-PD-1 therapy discontinuation in this group of patients. Methods This retrospective cohort study included patients diagnosed with advanced cSCC and treated with either cemiplimab or pembrolizumab from 2019 to 2024 at a single university-affiliated tertiary medical center. Results The cohort included 131 patients, with a 73% overall response rate. Among the 86 patients with either partial or complete response as the best response included in the final analysis, 40 (47%) patients had a treatment break for at least 3 months, and 46 (53%) continued without discontinuation to a maximal duration of 2 years. After a median follow-up of 29.9 months, 24 (60%) patients in the break group remained progression-free, systemic treatment-free, and alive throughout the follow-up. Four patients (10%) experienced disease progression. Among these, the best overall response was PR in three patients and CR in one patient. Nine (22.5%) patients died due to non-oncological reasons, two (5%) patients died from an unknown cause, and one (2.5%) due to treatment toxicity. The percentage of patients achieving CR was statistically significantly higher in the break group compared to the no-break group. Conclusions Our findings advocate for a more tailored approach to the duration of PD-1 inhibitor therapy in cSCC, potentially reducing burdens of overtreatment. Future studies regarding establishing robust predictors for safe treatment discontinuation are required to enhance decision-making in clinical practice.